2017
DOI: 10.1016/j.aquatox.2017.06.014
|View full text |Cite
|
Sign up to set email alerts
|

Pathway analysis of systemic transcriptome responses to injected polystyrene particles in zebrafish larvae

Abstract: Microplastics are a contaminant of emergent concern in the environment, however, to date there is a limited understanding on their movement within organisms and the response of organisms. In the current study zebrafish embryos at different development stages were exposed to 700nm fluorescent polystyrene (PS) particles and the response pathway after exposure was investigated using imaging and transcriptomics. Our results show limited spreading of particles within the larvae after injection during the blastula s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
62
1
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
3
2
2

Relationship

1
6

Authors

Journals

citations
Cited by 153 publications
(64 citation statements)
references
References 45 publications
0
62
1
1
Order By: Relevance
“…Besides, pathway analysis and signal‐net analysis revealed that PI3K/Akt, MAPK, and TNF signaling pathways were strongly influenced . When studying toxic effects of polystyrene microbeads in zebrafish larvae, transcriptome data showed that the genes related to alternative pathways of complement ( cfhl3 , cfhl4 , cfb , and c9 ) were up‐regulated . The combined analysis with the co‐localization of neutrophils and macrophages surround polystyrene microbeads suggested a close connection between MPs and immunological recognition in zebrafish larvae.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Besides, pathway analysis and signal‐net analysis revealed that PI3K/Akt, MAPK, and TNF signaling pathways were strongly influenced . When studying toxic effects of polystyrene microbeads in zebrafish larvae, transcriptome data showed that the genes related to alternative pathways of complement ( cfhl3 , cfhl4 , cfb , and c9 ) were up‐regulated . The combined analysis with the co‐localization of neutrophils and macrophages surround polystyrene microbeads suggested a close connection between MPs and immunological recognition in zebrafish larvae.…”
Section: Discussionmentioning
confidence: 98%
“…46 When studying toxic effects of polystyrene microbeads in zebrafish larvae, transcriptome data showed that the genes related to alternative pathways of complement (cfhl3, cfhl4, cfb, and c9) were up-regulated. 47 The combined analysis with the co-localization of neutrophils and macrophages surround polystyrene microbeads suggested a close connection between MPs and immunological recognition in zebrafish larvae. Our transcriptome data showed that the inflammatory/immune pathways were deeply influenced by PS-MPs, including PPAR signaling pathways, AMPK signaling pathways, Ras signaling pathway, Phospholipase D signaling pathway, N-Glycan biosynthesis, catalase, GSH, and other enzymes, which is consistent with the study of Lei et al 7 Exposure to some kind of MPs, such as polyamide, polyethylene, polypropylene, PVC, and polystyrene, demonstrated low casualty in Danio rerio but gut mucosa damage on the part of villi disruption and splitting of enterocytes and elevated GST enzyme activity throughout ten days of treatment.…”
Section: Validation By Quantitative Rt-qpcr and Elisamentioning
confidence: 97%
“…Previous studies indi-424 cated, however, that injected PSNPs can activate pathways related to immune responses when 425 injected into the yolk of 2 days old zebrafish embryos (700 nm PSNPs) as well as in fathead 426 minnow plasma (41 nm PSNP). 46,47 Because of the compliment activation by PSNP 46 , a much 427 earlier response by macrophages could occur, which is not captured after 24 h of exposure in 428 this study or alternatively plastic particles might be ingested by non-immune cells which was 429 exemplified by Hosseini and colleagues…”
mentioning
confidence: 93%
“…Transcriptome analysis of the zebrafish embryo after injecting the polystyrene particles led to the activation of complement system (Veneman et al . ). In the present circumstance of increased application of nanoparticles, liver transcriptome analysis demonstrated the harmful effect of iron oxide nanoparticles (Villacis et al .…”
Section: Current Status Of Transcriptomics In Aquaculturementioning
confidence: 97%
“…), microplastics (Veneman et al . ; Détrée & Gallardo‐Escárate ), human pharmaceuticals (Hampel et al . ) and pharmaceutical pollutants (Saaristo et al .…”
Section: Current Status Of Transcriptomics In Aquaculturementioning
confidence: 99%